Admissible relaxation in optimal control problems for infinite dimensional uncertain systems. (1992) - Ahmed, N. U.; Xiang, X.
Abstract : In this paper we present a result on admissible relaxation for a class of systems governed by an uncertain evolution equation on Banach space. We show that the set of original trajectories is dense in the set of relaxed trajectories and that under certain assumptions the relaxed system is equivalent to the original system.